Karakteristik Kulit Tersamak Dengan Bahan Penyamak Nabati Alternatif Studi : Perlakuan PH Asam Dan Basa Pada Larutan Penyamakan - Mutiar, Sri; Yusmita, Lisa; Aini, Nurul (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2024)
This study aims to determine the characteristics of tanned leather using alternative vegetable tanning agents from bark extracts and Acacia auriculiformis and Acacia mangium at pH 4 and 8. The research method uses the standard tanning method using salt preserved goat skin. Chemical analysis and physical testing of tanned leather refers to SNI-06-0463-1989-A and SNI 0234:2009. Based on the chemical analysis of tanned leather for both tanner extracts at pH 4, the tanned leather was produced imperfectly with low bound tannins and low wrinkle temperature. Tanned leather at pH 8 using A. auriculiformis and A. mangium extracts through single tanning has met the SNI standard.